Organizational behavior improving performance and commitment in the workplace - Colquitt, Jason; LePine, Jeffery A.; Wesson, Michael J. (McGrawHill/Irwin, 2013)
Now in its third edition, Colquitt-LePine-Wesson continues to offer a novel and innovative approach to teaching organizational behavior. The focus, tone, and organization of the book shows students that: OB really matters - The book opens with two chapters barely covered in other texts: job performance and organizational commitment. Those topics are critical to managers and students alike, and represent two of the most critical outcomes in OB. Each successive chapter then links that chapter's topic back to those outcomes, illustrating why OB matters in today's organizations